Physiochemical Analysis, Antioxidant Effects, and Sensory Characteristics of Quark Cheese Supplemented with Ginseng Extract - Kim, Kee-Tae (Food Sci Anim Resour, 2019)
The objective of this study was to evaluate physicochemical and sensory properties, the texture profile, and antioxidant activity of ginseng extract-supplemented quark cheese as a new cheese product intended to improve public health. After addition of less than 1.0% ginseng extract, the moisture content of quark significantly decreased, while fat and protein levels increased, although microbial counts and lactose and ash contents were not affected significantly (p<0.05). In terms of color, L* values decreased significantly with increasing concentration of ginseng extract, while a* values increased significantly (p<0.05). The results of texture profiling showed that cohesiveness and springiness were unaffected, whereas hardness, gumminess, and chewiness increased significantly. The 2,2′-azino-bis-3-ethylbenzothiazoline-6-sulphonic acid (ABTS) radical-scavenging activities of the cheese fortified with 0%, 0.5%, or 1.0% of the ginseng extract were 4.22%±0.12%, 20.14%±1.34%, and 56.32%±1.54%, respectively. The results of sensory analysis indicated that bitterness, ginseng odor, and aftertaste significantly improved with increasing concentration of ginseng extract (p<0.05). However, there was no significant difference in the overall quality attributes of quark cheese between the no-supplement control and samples with less than 0.5% of the ginseng extract (p>0.05), suggesting that these products could help to promote public health as functional foods.